PERAN AUDITOR INTERNAL PEMERINTAH DAERAH, EFEKTIVITAS PENGENDALIAN INTERNAL, BUDAYA ORGANISASI TERHADAP PENCEGAHAN KECURANGAN - Aisyah, Gusti Willies; Taufan, Januar (Media Riset Bisnis Ekonomi Sains dan Terapan, 2024)
This study aims to empirically prove the effect of the role of local government internal auditors, the effectiveness of internal control, and organizational culture on fraud prevention. This research uses a quantitative approach. The data collection method used is primary data with the field survey method. The population in this study were employees who worked at Inspektorat Kotabaru District. The sampling technique used nonprobability sampling with saturated sampling technique. Data collection was carried out by sending google forms to respondents as many as 36 respondents. The data was processed using SPSS version 25.The results of this study partially show that the role of local government internal auditors has a positive and not significant effect on fraud prevention, the effectiveness of internal control has a positive and significant effect on fraud prevention, and organizational culture has a positive and significant effect on fraud prevention.. Keywords : The Role of Local Government, The Effectiveness of Internal Control, Organizational Culture, Fraud Prevention